Psychometrical properties of the Antisocial and Criminal Behavior Scale in adolescents - Andreu Rodríguez, José Manuel; Peña, María E. (Anales de Psicología / Annals of Psychology, 2013)
The present study focuses on the metric quality of a scale designed for measuring antisocial behavior. The scale was applied to a sample composed by 640 adolescents of both sexes with an age range between 12 and 18 years old. All participants in the study belonged to schools from the Community of Madrid and their participation in the research was completely confidential and anonymous. The application of the confirmatory factor analysis showed a one-dimensional structure composed by a general dimension of antisocial behavior. The internal consistency showed by the scale was broadly satisfactory. Implications of results concerning the factor structure and construct validity of the scale in adolescents are discussed.